A conductive channel size comparison of silicon dielectric and amorphous silicon antifuses - Chen, K.-L. (1993 International Symposium on VLSI Technology, Systems, and Applications Proceedings of Technical Papers, 1993)
The physical size of an antifuse conductive channel is determined through the electrical characterization by using sidewall antifuse structures. The relationship of a programmed 'ON' antifuse conductive channel size as a function of the programming current is established for both metal-metal amorphous silicon antifuses and poly-poly nitride/oxide antifuses. The result shows that the metal amorphous silicon antifuse requires at least 6 times higher programming current than the silicon dielectric antifuse to reach the same conductive channel size with 2000 AA diameter. The programming current ratio for these two types of antifuses increases with increasing antifuse conductive channel size.< >